IMF Staff Papers, Volume 52, No. 3. (IMF Staff Papers; IMF Staff Papers, 2005)
This last issue for 2005 comprises seven new papers, including a contribution to the journal's occasional Special Data Section about domestic debt markets in Sub-Saharan Africa, and also an in-depth look at the internal job market for entry-level economists at the IMF. The remaining articles cover toics as diverse as: modeling of asset markets, exchange rates in developing countries, international bank claims on Latin America, the effectiveness of "early warning" systems, and the use (by emerging market countries) of the IMF's Special Data Dissemination Standard (SDDS).